STRATEGY ANALYSIS OF MUHAMMADIYAH GAMPING HOSPITAL FACING NATIONAL HEALTH INSURANCE - Ario Tejosukmono (Universitas Muhammadiyah Semarang, 2017)
National Social Security System, Act Number 40 Year 2004 mandated that National Social Security System as National Health Insurance starting January 1, 2014. As a private hospital that follow the program, Muhammadiyah Gamping Hospital has to prepare strategies for it. This study aims to analyze the strategy of Muhammadiyah Gamping Hospital facing National Health Insurance. The analysis used a quantitative of Strenght, Weakness, Opportunities, Threats (SWOT) analysis to determine the actual position of the hospital so it can choose the right strategies. Data collection using in-depth interview method, quesioner, and document review. The sample of the research are 4 people who are the directors of Muhammadiyah Gamping Hospital. Quantitative SWOT analysis puts the hospital in quadrant III, which means that the hospital is in a position of having many weaknesses but has many opportunities, then they have to make a strategy changes. In this research there are many strategies that can be done.Some strategies are making Clinical Pathway, recalculate unit cost and utilization Hospital Information Technology and bridging with BPJS system. This study show that Muhammadiyah Gamping Hospital has to make a strategy changes according to the position of hospital in quadrant III. Keywords: SWOT analysis; Hospital strategy; National Social Security.